Presence of toxic microbial metabolites in table olives - Medina-Pradas, Eduardo; Arroyo-López, Francisco Noé (Frontiers in Microbiology, 2015)
Table olives have an enormous importance in the diet and culture of many Mediterranean countries. Albeit there are different ways to produce this fermented vegetable, brining/salting, fermentation and acidification are common practices for all of them. Preservation methods such as pasteurization or sterilization are frequently used to guarantee the stability and safety of fermented olives. However, final products are not always subjected to a heat treatment. Thus, microbiota is not always removed and appropriate levels of acidity and salt must be obtained before commercialization. Despite the physicochemical conditions not being favourable for the growth of foodborne pathogens, some illness outbreaks have been reported in the literature. Street markets, inappropriate manipulation and storage conditions were the origin of many of the samples in which foodborne pathogens or their metabolites were detected. Many authors have also studied the survival of pathogens in different styles of table olive elaboration, finding in general that olive environment is not appropriate for their presence. Inhibitory compounds such as polyphenols, low availability of nutrients, high salt content, low pH levels, bacteriocins or the addition of preservatives act as hurdles against undesirable microorganisms, which contribute to obtaining a safe and good quality product.